UX Redesign aplikace Goodreads z pohledu vybraného uživatelského scénáře - Holotova, Dariia; Dědic, Filip; Vacková, Tereza; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2023)
This bachelor's thesis presents a UX redesign of the Goodreads application (version 2022) for specific user scenarios, each representing different types of users and their specific needs and expectations from the Goodreads app. The first scenario represents a user who is interested in tracking their reading progress, while the second scenario represents a user who is interested in organizing their physical book collection. The third scenario represents a user who is interested in discovering new books and authors through social media. The primary objective was to improve the user experience of the application and make it more user-friendly. The theoretical part of the thesis discusses the concepts of UX and UI design, their differences, and the design process, various applications that designers use in their work. Furthermore, this work reviews the history of Goodreads, its direct and indirect competition, and the challenges it faces. The practical part of the study followed a structured approach to design and refine the user experience of the Goodreads app. It started with wireframing, selecting a grid, and preparing the components, colors, and fonts to be used. Screens were then designed for each scenario, and proposed UX changes were made based on user feedback and basic UX principles. The resulting design was compared to the current Goodreads app, and an interactive prototype was created to demonstrate how it would work in practice. In addition to redesign of the Goodreads application, this bachelor's thesis also includes user experience testing. A total of six users participated in the testing process, providing feedback on the proposed UX changes and suggesting additional improvements. The output of the work includes three user flows in Figma, along with an interactive prototype. These prototypes serve as a visual representation of the new design, which can be used to gather feedback from potential users.
Overall, the thesis aimed to provide an analysis of the Goodreads application and develop a user experience redesign that would improve the overall user experience.
Vedoucí práce: Filip Dědic
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: multimédia v ekonomické praxi [obor bakal. práce]; bakalářské práce; bachelor's theses